2020
DOI: 10.1253/circj.cj-20-0935
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Epicardial Adipose Tissue in the Pathogenesis of Coronary Atherosclerosis ― An Update on Recent Findings ―

Abstract: Adipose tissue serves not only as an energy store or a mechanical cushion, but also as an endocrine organ. Recent evidence revealed that perivascular adipose tissue is involved in vascular homeostasis and pathophysiology of adjacent arteries by producing various adipokines. Epicardial adipose tissue (EAT) is located between the surface of the heart and the visceral layer of the pericardium and surrounds the coronary arteries. Many clinical studies suggest that an increase in EAT volume is associated with coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Adipose tissue (AT) is universally regarded as an endocrine and paracrine organ that synthesizes biologically active molecules. Adipocytokines are involved in various processes, including inflammation, fibrosis, and atherogenesis [2][3][4]. It has been shown that local fat depots, such as epicardial (EAT) and perivascular AT (PVAT), are associated with increased cardiovascular events, independent of traditional risk factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue (AT) is universally regarded as an endocrine and paracrine organ that synthesizes biologically active molecules. Adipocytokines are involved in various processes, including inflammation, fibrosis, and atherogenesis [2][3][4]. It has been shown that local fat depots, such as epicardial (EAT) and perivascular AT (PVAT), are associated with increased cardiovascular events, independent of traditional risk factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have proposed that physical exercise can reduce PAT due to reductions in proinflammatory adipokines and improvements of inflammatory factors in the milieu of the coronary vessel wall (28)(29)(30). Other studies have reported that sodium-glucose cotransporter 2 inhibitors and glucagon-like peptide-1 receptor agonists can reduce PAT in patients with type 2 diabetes (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The adipose tissue surrounding the heart involves two types of depots, the pericardial adipose tissue (PAT) and the EAT, even if the nomenclature is confusing, as some researchers use the terms paracardial or intrathoracic or mediastinal for pericardial fat, and the term pericardial fat to indicate the combination of paracardial fat with EAT [ 23 ]. PAT rests on the external surface of the pericardial fibrous layer, consists of adipocytes originating from the primitive thoracic mesenchyme, and is vascularized by non-coronary arteries.…”
Section: Anatomical Features and Functional Properties Of Eatmentioning
confidence: 99%